Prevalência de soropositividade para hepatite B e C em gestantes - Fernandes, Carla Natalina da Silva; Alves, Michelly de Melo; Souza, Michelly Lorrane de; Machado, Gleyce Alves; Couto, Gleiber; Evangelista, Renata Alessandra (Revista da Escola de Enfermagem da USP, 2014)
The aim of the study was to identify the prevalence of hepatitis B and C seropositivity in pregnant women attended in a public maternity hospital located in Catalao-GO from 2005 to 2009. Descriptive, exploratory study conducted through patients` hospital records. For data analysis, we used SPSS version 18.0. The confidence interval (CI) was calculated using the Person χ² test, considering a significance level of 5% (p